2007
DOI: 10.1002/dev.20242
|View full text |Cite
|
Sign up to set email alerts
|

Maternal anesthesia via isoflurane or ether differentially affects pre‐and postnatal behavior in rat offspring

Abstract: Our understanding of prenatal behavior has been significantly advanced by techniques for direct observation and manipulation of unanesthetized, behaving rodent fetuses with intact umbilical connections to the mother. These techniques involve brief administration of an inhalant anesthesic, enabling spinal transection of the rat or mouse dam, after which procedures can continue with unanesthetized dams and fetuses. Because anesthetics administered to the mother can cross the placental barrier, it is possible tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…Notably, the negative effects of prolonged or excessive exposure to anesthetics on the central nervous system, especially on memory and learning in children and infants, have been broadly represented [4,5]. Isoflurane (ISO), as one of the most used inhalation anesthetics, simply crosses the placental barrier and decreases the regeneration of neuronal stem cells and inhibits the proliferation, sustenance, and development of human neural progenitor cells at clinically relevant concentrations [6][7][8]. In recent years, ISO-induced neuronal damage in the developing brain has received more and more attentions [9].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the negative effects of prolonged or excessive exposure to anesthetics on the central nervous system, especially on memory and learning in children and infants, have been broadly represented [4,5]. Isoflurane (ISO), as one of the most used inhalation anesthetics, simply crosses the placental barrier and decreases the regeneration of neuronal stem cells and inhibits the proliferation, sustenance, and development of human neural progenitor cells at clinically relevant concentrations [6][7][8]. In recent years, ISO-induced neuronal damage in the developing brain has received more and more attentions [9].…”
Section: Introductionmentioning
confidence: 99%
“…Especially, exposure to sevoflurane inhibits neurogenesis in the brain of foetal mice and impairs subsequent learning and memory ability . Isoflurane, another inhalational anaesthetic, decreases the self‐renewal of neuron stem cells and reduces the survival, proliferation and differentiation of human neural progenitor cells . These studies suggested that inhalational anaesthetic could lead significant effect to development and cause serious problems.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, any residual effects of general anesthesia may have affected pup behavior. However, isoflurane anesthesia has been shown to have no significant effects on breathing frequency or blood pH within 2 hr of cesarean delivery of fetal rats [59], and there is no significant difference between cesarean-delivered and vaginal-delivered pups on measures of pO 2 , brain lactate, blood pH, pCO 2 , and brain ATP levels within 4 hr after delivery [60]. Further, the E21 rat has been shown to be able to induce protective lung antioxidant enzymes and lung surfactant responses that are comparable to the full-term rat [61].…”
Section: Discussionmentioning
confidence: 99%